PENGARUH PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP), MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN (BKPP) KOTA SEMARANG - Putri Elviana; Artha Febriana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study was conducted to analyze and prove the effect of providing additional employee income (TPP), work motivation and work environment at BKPP Semarang City with a population of 78 employees. In this study, the sampling method used was census. The data collection technique in this study used a questionnaire given to the respondents while the data analysis technique used was multiple regression analysis. The results of this study state that TPP has a positive and insignificant effect on employee performance, motivation has a negative and insignificant effect, while the work environment has a positive and significant effect on employee performance.